RETRACTED: The Impact of Geopolitical and Pandemic Risks on Tourist Inflows: Evidence From Asia-Pacific Region - Wang, Hong; Khan, Yousaf Ali; Mouldi, Abir; Abou El Khier, Bothaina Samih; Guo, Wei (Frontiers in Environmental Science, 2022)
The aim of this research is to investigate the impact of major risks such as geopolitical and pandemics risks on tourism industry in selected countries of Asia-Pacific. The results were obtained using a sample of ten neighboring countries in the period 1996 to 2018. Diagnostic tests confirmed the existence of spatial interaction between model variables for these countries. According to the results, the economic growth, internally and in neighboring countries leads to an increase in the influx of tourists. Whereas, increased domestic prices will reduce the influx of domestic tourists, rising prices in neighboring countries intensify tourists' arrival of the country. Furthermore, results reveal that, domestic geopolitical and pandemics risks lead to a decrease in tourist arrivals. In addition, while pandemics risks in neighboring countries do not have a significant effect on tourist arrivals, geopolitical risks in neighboring countries lead to more domestic tourists' arrival.